2018
DOI: 10.1590/1516-3180.2018.0145240418
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning and quality of life among children with anxiety disorder and healthy controls. A cross-sectional study

Abstract: We found that both family functioning and quality of life among children with AD were negatively affected. However, further studies with larger sample sizes are required to reach stronger conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The first and only meta-analysis to compare QoL in adults between anxious and non-clinical controls identified 23 studies (N = 2892) and, as expected, yielded large effect sizes suggesting poorer QoL among anxious adults (Olatunji et al, 2007). Not surprisingly, among the few studies conducted in young people, overall QoL has also been found to be inversely associated with anxiety in young people (Öztürk et al, 2018;Raknes et al, 2017). In cross-sectional studies, and in comparison with non-anxious children and adolescents, anxious young people have been found to report poorer QoL across multiple dimensions (e.g., physical wellbeing, psychological well-being, autonomy and parent child relations, social support and peers and school environment (Raknes et al, 2017;Telman et al, 2017).…”
Section: Quality Of Lifementioning
confidence: 82%
See 1 more Smart Citation
“…The first and only meta-analysis to compare QoL in adults between anxious and non-clinical controls identified 23 studies (N = 2892) and, as expected, yielded large effect sizes suggesting poorer QoL among anxious adults (Olatunji et al, 2007). Not surprisingly, among the few studies conducted in young people, overall QoL has also been found to be inversely associated with anxiety in young people (Öztürk et al, 2018;Raknes et al, 2017). In cross-sectional studies, and in comparison with non-anxious children and adolescents, anxious young people have been found to report poorer QoL across multiple dimensions (e.g., physical wellbeing, psychological well-being, autonomy and parent child relations, social support and peers and school environment (Raknes et al, 2017;Telman et al, 2017).…”
Section: Quality Of Lifementioning
confidence: 82%
“…That is, whereas some scholars may be using more global scales of impairment, others may be relaying on multidimensional QoL scales to index functioning across specific domains (e.g., Öztürk et al, 2018). To this end, in the current review, only three studies compared children and/or adolescents with anxiety disorders to healthy controls on QoL (Öztürk et al, 2018;Raknes et al, 2017;Telman et al, 2017). The three studies evaluated QoL using different scales but converging on key dimensions including physical, emotional, social, and school.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as genetics, neurotransmitters abnormalities, maladaptive and irrational thoughts, having unpleasant or traumatic experiences, chronic illnesses or recent diagnoses of disease, daily stress, consumption of alcohol and illegal drugs, and lack of ability and inexact emotion regulation strategies, contribute to the appearance of anxiety disorders (Foroudifard et al, 2020;Halgin & Whitbourne, 2012;Huffstutler, 2021;Loevaas et al, 2018;Mahardika & Ediati, 2019;Narmandakh, Roest, de Jonge, & Oldehinkel, 2020;Nevid, Rathus, & Greene, 2018;Quiñones-Camacho & Davis, 2019;Sackl-Pammer et al, 2019). Other things such as female, family dysfunction, lack of social support, low economic status, and history of psychopathology in parents indicate links to increased anxiety risk (Mondin et al, 2013;Öztürk, Özyurt, & Akay, 2018;Shao et al, 2020;Wang, Chen, Tan, & Zhao, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Family function reported significantly correlated and could be predictive for individual anxiety disorders (Chapman & Woodruff-Borden, 2009;Shao et al, 2020). Correlation that has family function and anxiety is negative so that the better a family performs, the lower the anxiety level (Mahardika & Ediati, 2019;Öztürk et al, 2018). Some dimension of family function is associated with certain disorders: high affective involvement and problem solving associated with opportunities of severe depression and social phobias, good communication correlates with a low chance of overall anxiety disorders, behavioral controls correlate with social phobias and oppositional defiant disorders (Oltean, Perlman, Meyer, & Ferro, 2020).…”
Section: Introductionmentioning
confidence: 99%